The Concept of the Artistic Canon in Ancient Art as an Example of the Implied Logic in the Aesthetic Experience Unfolding - Весна Монд-Козловська (Вісник КНУКіМ: Серія Мистецтвознавство, 2025)
The aim of the article is to develop the cognitive stand claiming that the ontological concept of logos, while viewed as a funding and constitutive number, does lie indeed at the very core of all creative processes. The phenomenon can be immediately recognised in logical relational thinking which, paraphrasing Eli Siegel (n.d.), reveals where things have to do with each other, what are their points of sameness and difference and accordingly, relation in art is the revelation of how the objects have to do with each other. Thus, first and foremost, the mathematical ratio is called in this frame of reasoning a canon. Its visual evidence being discussed in the ongoing research is the shape of the ancient Greek vase and its mathematical construction. Results. In the act of the aesthetic perception, together with a producer of the piece of art, yet in a diachronous, say historical way, the onlookers are entering, if intentionally, a stream of a creative process. At that very moment they are diachronically experiencing the same powerful mathematical laws that were set in motion by the artist that was once determined to render the working of this material world. Such a phenomenon points to the fact that great pieces of art have a significant impact on the human mind with their ability to both restore and maintain an order in the human psyche, every so often disturbed by multifarious, both internal and external, factors. Scientific novelty. Although this article is embedded in the so far existing research work on the dynamic symmetry of the Greek vase, carried out by J. Hambidge in the 20th century, nevertheless, it brings an independent academic outcome that results from the author’s previous research into overlapping lines of the aesthetic experience and the feeling of the sacred. Moreover, the study in question approaches a subject matter being researched from the strict neuroaesthetic perspective. The nature of mind and a monistic concept of the human being are discussed while it is offered to follow phenomenologically a development of the aesthetic experience that had been structured in its consequential course by Roman Ingarden (1966). Conclusions. Logic is an exercise of thinking even if its theorems and workings are not so explicit in the body of the piece of art, but are hidden under the surface of the masterworks created by a gifted and skillful personality. Logic aims at purifying the human mind, atuning it with the universal ontic laws. Practicing logic in whatever way, through contemplation of art in the first place, it proves the human’s mental endeavour to restore the unity of the world that logos entrenches and safeguards.